CO2 methanation on hard-templated NiOCeO2 mixed oxides. (10th August 2017) - Atzori, L.; Cutrufello, M.G.; Meloni, D.; Monaci, R.; Cannas, C.; Gazzoli, D.; Sini, M.F.; Deiana, P.; Rombi, E.
Abstract: Mesostructured NiOCeO2 mixed oxides, with Ni loadings in the range 5–35 wt% (gNi /gCeO2 ), were synthesized by the hard template procedure using SBA-15 as the template. A hard-templated CeO2 was also prepared and used as the support for depositing Ni (5–35 wt%) by impregnation. Two NiOAl2 O3 catalysts were synthesized for comparison, by impregnating nickel on a commercial γ-alumina. All the samples were characterized by different techniques as to their chemical composition, structure, morphology, texture, and redox features. The catalytic performance was investigated in the CO2 methanation reaction after mild reduction pretreatment (H2 at 400 °C for 1 h). Catalytic testing was performed under atmospheric pressure, 300 °C, 72, 000 cm 3 h −1 gcat −1, and stoichiometric H2 /CO2 molar ratio. High catalytic activity, with CH4 selectivity values ≥ 93 mol%, was obtained with the NiOCeO2 mixed oxides (CO2 conversions up to 76 mol%). When γ-Al2 O3 was used as the support, catalysts with low activity (CO2 conversion ≤ 20 mol%) were obtained. On selected samples, additional catalytic runs were also performed for reaction times up to 30 h or with a higher space velocity value. The catalytic results were explained by taking into account the role of the nickel-ceria interactions both during the reduction of NiO and in the reactants activation. Graphical abstract: Highlights: Mesostructured SBA-15-templated NiOCeO2 mixed oxides were prepared. The NiOCeO2 catalysts were very active and selective for CO2 methanation. Hard template method led to a better dispersion of Ni compared to impregnation. Ni 0 crystal size is important to ensure high catalytic activity in any reaction condition. CeO2 support performed better than Al2 O3 in preventing agglomeration of Ni 0 particles.